The Ameliorative Effects of Allopurinol on Paraquat-Induced Pulmonary Fibrosis in Rats - Saeedeh Shariati; Mohammad Javad Khodayar; Aliasghar Hemmati; Mehdi Goudarzi; Milad Kiani; Anahita Rezaei (Tabriz University of Medical Sciences, 2019)
Background: Pulmonary ﬁbrosis is described as a chronic idiopathic inﬂammatory disease of the interstitial lungs. It is associated with a potentially fatal prognosis, and patients show insignificant response to treatment. To treat paraquat (PQ)-induced pulmonary injury and fibrosis, multiple approaches have been used. We aimed to determine the effects of allopurinol (Allo), a xanthine oxidase inhibitor, on PQ-induced pulmonary fibrosis in rats. Methods: A total of 30 female Sprague-Dawley rats were divided randomly into five groups (200±20 g). Group 1 (control) and group 2 (PQ group) were intraperitoneally administered PQ (20 mg/kg) once on day seven without any treatment, while groups 3-5 orally received 50, 100, and 200 mg/kg of Allo seven days before and three weeks following the administration of PQ, respectively. The animals were sacrificed three weeks after PQ administration. For the histopathological analysis and assessment of serum malondialdehyde (MDA) and hydroxyproline (HP) contents, the animals' blood and lungs were collected. Results: The PQ group showed significantly higher lung HP, serum MDA, and lung index in comparison with the control. Treatment with Allo, especially at 100 and 200 mg/kg, decreased HP, MDA, and lung index significantly, compared to the PQ group. Allo could prevent inflammatory cell infiltration, presence of fibroblasts, and PQ-related alveolar thickening. Conclusion: The results revealed that Allo has potential protective effects on PQ-related pulmonary fibrosis, and the role of xanthine oxidase in the exacerbation of PQ-induced pulmonary fibrosis was confirmed.